Przedsiębiorstwo w dobie globalizacji - Czupiał, Jerzy (Enterprises in the Age of Globalization, 2008)
The development of enterprises and their expansion across borders have become the main factor of globalization. Three waves of globalization have shaped in different ways markets, competitions and enterprises as well. The contemporary third wave of globalization has six distinctive features forming activities of enterprises and the nature of leadership. These are: global thinking, valuing, cultural differentiation, the need of developing technological sense, building partnerships and alliances, and developing social responsibility of enterprises. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 40-50